PENGARUH KESADARAN WAJIB PAJAK DAN TINGKAT PENGHASILAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI PADA KPP PRATAMA KOTA PANGKALPINANG) - Devandi, Edwar; Tri Setyo Mulyani, Hendarti; Ahmad Agin, Arka'a (Jurnal Akuntansi Bisnis Dan Keuangan, 2020)
This is a bachelor thesis compiled by Edwar Devandi, student identification number 540160015, titled in Indonesian: "Pengaruh Kesadaran Wajib Pajak dan Tingkat Penghasilanterhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Pada Wajib Pajak Kota Pangkalpinang)" . This research was conducted in September to february 2018 in the city of Pangkalpinang. The purpose of this study was to determine The influence of taxpayers and the level of income on compliance of individual taxpayers (studies at the pratama municipal tax service office in pangkalpinang). This study uses quantitative data analysis and multiple linear regression. The number of taxpayers increases for years but it is not balanced with the level of tax compliance. This study aims to empirically examine and analyze The influence of taxpayers and the level of income on compliance of individual taxpayers. This research was conducted by a survey method of individual taxpayers in the city of Pangkalpinang. Samples were obtained using random sampling technique. Methods of data collection through questionnaires and data were analyzed using multiple linear regression analysis. Regression test results found that the variable awareness of taxpayers and the level of income has a positive effect on compliance of individual taxpayers.